2023
DOI: 10.1155/2023/5277425
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Investigation and Microanalysis of Black Cotton Soil Amended with Guar Gum and Polyethylene Terephlate Fibre

S. Sathyapriya,
M. S. Abdul Fasith,
P. Senthil Kumar
et al.

Abstract: Polymer-based soil stabilization has fascinated substantial interest in the field of research intending to gain a better knowledge of the anticipated soil characteristics after polymer treatment. Intricate research on the engineering performance of expansive soil which is highly challenging due to its swell and shrink nature based on variations in water regime, treated with guar gum, a biopolymer made from gum along with polyethylene terephthalate fibre, one of the most generated plastics, resulting in massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The optimal dosage of guar gum biopolymer was mixed with polyethylene terephthalate fibres, and the effect on soil geotechnical properties was carried out separately. According to Sathyapriya et al (2023), it was demonstrated that there is a reduction in plasticity index, swelling, maximum dry density (MDD), and compressibility of soils treated with 0.5% guar gum biopolymer and 1.6% polyethylene terephthalate fibres. On the other hand, the California Bearing Ratio (CBR) of soils treated with 0.5% guar gum biopolymer and 1.6% polyethylene terephthalate fibres increases.…”
Section: Polyethylene (Pe) Fibrementioning
confidence: 99%
“…The optimal dosage of guar gum biopolymer was mixed with polyethylene terephthalate fibres, and the effect on soil geotechnical properties was carried out separately. According to Sathyapriya et al (2023), it was demonstrated that there is a reduction in plasticity index, swelling, maximum dry density (MDD), and compressibility of soils treated with 0.5% guar gum biopolymer and 1.6% polyethylene terephthalate fibres. On the other hand, the California Bearing Ratio (CBR) of soils treated with 0.5% guar gum biopolymer and 1.6% polyethylene terephthalate fibres increases.…”
Section: Polyethylene (Pe) Fibrementioning
confidence: 99%